The household economic burden of non-communicable diseases in 18 countries - Murphy, A; Palafox, B; Walli-Attaei, M; Powell-Jackson, T; Rangarajan, S; Alhabib, KF; Avezum, AJ; Calik, KBT; Chifamba, J; Choudhury, T; Dagenais, G; Dans, AL; et al. (BMJ Publishing Group, 2020)
Background Non-communicable diseases (NCDs) are the leading cause of death globally. In 2014, the United Nations committed to reducing premature mortality from NCDs, including by reducing the burden of healthcare costs. Since 2014, the Prospective Urban and Rural Epidemiology (PURE) Study has been collecting health expenditure data from households with NCDs in 18 countries.